Kinetics of ethylene polymerization over titanium catalyst supported on bimetallic carrier MgCl2(THF)2/AlEt2Cl - Ochędzan-Siodłak, W.; Nowakowska, M. (Polimery, 2022)
Ethylene polymerization kinetics over TiCl4/Et3Al catalyst supported on MgCl2(THF)(2)/AlEt2Cl was investigated. The investigated catalyst system shows the presence of two kinds of the active sites: the unstable, low active classic sites, and the high active sites, supported on the bimetallic complex. The former can be eliminated from the catalyst system by means of a prepolymerization reaction with 1-pentene. Kinetics analysis allowed to determine: overall concentration of active centers (n(k), stable + unstable centers), concentration of stable active centers (n*) chain propagation rate constant (k(p)), and chain transfer rate constant (k(tr)). It was concluded that number of stable active centers in the primary catalyst (prior to prepolymerization) is much higher than the number of eliminated active unstable centers (73% compared with 27%).